BANKS' FUNCTIONING WITHIN THE FRAMES OF NATIONAL MODELS OF SOCIAL RESPONSIBILITY CONCEPT - Irina V. Vashchekina (Plekhanov Russian University of Economics, 2017)
The article deals with interaction of bank and credit organizations and other entities in the process of their functioning in the present structure of commercial, industrial and social links. The impact of bank as a component of the banking system on shaping positive atmosphere in business and public life is multi-sided. A responsible bank can affect partners and motivate them to pursue social policy aimed at resolving social problems, which in the end could provide an opportunity for the whole group of enterprises to cooperate with local authorities, governmental structures and public organizations. The author compares principles of corporate social responsibility which exist in different countries and based on socio-cultural peculiarities of society development, such as economic, geographic, historic, ethical, humanitarian. These models are grouped within the frames of typical models.